Serotonergic Modulation of Absence-Like Seizures in Groggy Rats: a Novel Rat Model of Absence Epilepsy - Yukihiro Ohno; Nobumasa Sofue; Takuji Imaoku; Eri Morishita; Kenta Kumafuji; Masashi Sasa; Tadao Serikawa (Elsevier, 2010)
To explore the role of the serotonergic system in modulating absence seizures, we examined the effects of 5-HT1A and 5-HT2 agonists on the incidence of spike-and-wave discharges (SWD) in Groogy (GRY) rats, a novel rat model of absence-like epilepsy. GRY rats exhibited spontaneous absence-like seizures characterized by the incidence of sudden immobile posture and synchronously-associated SWD. The total duration of SWD in GRY rats was about 300 - 400 s/15-min observation period under the control conditions. However, the incidence of SWD was markedly reduced either by the 5-HT1A agonist (±)-8-hydroxy-2-(di-n-propylamino)-tetralin [(±)8-OH-DPAT] or the 5-HT2 agonist (±)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane [(±)DOI]. The 5-HT reuptake inhibitors, fluoxetine and clomipramine, also inhibited the SWD generation. In addition, the inhibitory effects of (±)8-OH-DPAT and (±)DOI were reversed by WAY-100135 (5-HT1A antagonist) and ritanserin (5-HT2 antagonist), respectively. The present results suggest that the serotonergic system negatively regulates the incidence of absence seizures by stimulation of 5-HT1A and 5-HT2 receptors. Keywords:: absence seizure, 5-HT1A receptor, 5-HT2 receptor, Groggy rat, spike-and-wave discharge